2013
DOI: 10.14260/jemds/566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Role of Preoperative Laparoscopy in Abdominal Malignancies.

Abstract: BACKGROUND AND AIMS: Many surgeons worldwide had challenging experience of facing an unexplainable and uncertain diagnosis or staging of abdominal malignancies. Laparoscopic visualisation techniques have improved dramatically and had led to reassessment of the laparoscope for use in the staging of intraabdominal malignancies. To evaluate place of preoperative laparoscopy as an additional tool to diagnose, assess staging and operability of intraabdominal tumors. SETTINGS AND DESIGN: A prospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the placebo effect of laparoscopy may explain at least partly the patient's pain relief. 25 In our study 43 (86%) patient had pathological findings identified at the time of laparoscopy. Miller et al reported that laparoscopy provided diagnoses in 89.8% of patients.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the placebo effect of laparoscopy may explain at least partly the patient's pain relief. 25 In our study 43 (86%) patient had pathological findings identified at the time of laparoscopy. Miller et al reported that laparoscopy provided diagnoses in 89.8% of patients.…”
Section: Discussionmentioning
confidence: 56%
“…Detail visualization of surface anatomy of intra-abdominal organs and establishment of intra-abdominal pathology became possible with the help of diagnostic laparoscopy for the surgeons. Specific advantage of laparoscopy for both the surgeons and the patients is that it provides specific answers related to pathology and confirms that nothing serious is found intra abdominally [8].…”
Section: Discussionmentioning
confidence: 89%
“…In case of diagnostic uncertainty, laparoscopy may help to avoid unnecessary laparotomy, provides accurate diagnosis, helps to plan surgical treatment, improves the outcome in the majority of patients with chronic abdominal pain and allows surgeons to diagnose and treat many abdominal conditions that cannot be properly managed otherwise [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most common organic disorders include intestinal adhesions, biliary causes, and appendicular causes, while functional disorders include irritable bowel disease, functional dyspepsia, and various motility disorders. 3 In spite of strong diagnostic workups, 40% of the patients with chronic abdominal pain did not have specific diagnosis at the end. 4 Many patients remain undiagnosed even after excluding the common disorders by meticulous investigations, and pose a significant diagnostic challenge to the physician.…”
Section: Introductionmentioning
confidence: 99%